Motivation to recover for adolescent and adult eating disorder patients in residential treatment. (13th April 2021) - Manwaring, Jamie; Blalock, Dan V.; Le Grange, Daniel; Duffy, Alan; McClanahan, Susan F.; Johnson, Craig; Mehler, Philip S.; Plotkin, Millie; Rienecke, Renee D.
Abstract: Objective: This study aimed to assess how baseline motivation to recover impacts eating disorder (ED) and comorbid symptoms at end‐of‐treatment (EOT) for adolescents and adults in inpatient/residential treatment. Method: Two hundred and three adolescent ( M = 15.90) and 395 adult ( M = 25.45) patients with a Diagnostic Statistical Manual, 5th edition ED diagnosis completed the Decisional Balance Scale (DBS) at baseline, and psychosocial measures (ED symptoms, anxiety, depression, obsessive–compulsive disorder symptoms), and %body mass index (kg/m 2 ; BMI) or median %BMI (for adolescents) at baseline and EOT. Results: The DBS Avoidance Coping and Burdens subscales at baseline were significantly lower for adolescents than adults ( p < 0.001), whereas the DBS Benefits subscale at baseline did not significantly differ between subsamples ( p = 0.06). Motivation to recover via DBS subscales was a more reliable predictor of EOT outcomes for both ED and comorbid psychopathology in adults (significant predictor in 19 of 54 total analyses, and 4 significant associations post‐Bonferroni correction) than adolescents (significant predictor in 5 of 54 total analyses, and 1 significant association post‐Bonferroni correction). Conclusions: Baseline motivation to recover may be an important predictor of outcome for adult patients in inpatient/residential treatment but does not appear associated with outcomes for adolescent patients. Highlights: The Decisional Balance Scale (DBS) Avoidance Coping and Burdens subscales at baseline to inpatient/residential treatment were significantly lower for adolescents than adults ( p < 0.001), whereas the DBS Benefits subscale at baseline did not significantly differ between samples ( p = 0.06). DBS Burdens subscale did not significantly predict outcome in the adult sample. Motivation to recover was a more reliable predictor of both eating disorder and comorbid psychopathology in adults than adolescents.